Comparison of water quality at the upstream and downstream points of the Sin River - خلوف, نسرين (Latakia University Journal -Engineering Sciences Series, 2024)
The aim of this research is to evaluate the water quality of the upstream and downstream points of the Sin River using NSF WQI, weighted arithmetic and Canadian index techniques. For this purpose, samples were taken from the source point (Lake Al-Sin) and the downstream point (near the sea). The following parameters were measured: temperature, PH, iron (Fe), copper (Cu), and manganese (Mg), nitrate, nitrite... Water samples were collected on a monthly basis for one year. The three quality indicators were calculated at each point upstream and downstream. The results showed that the water at the upstream point was acceptable and deviates somewhat from natural water. At the downstream point, the quality of the water according to the indicators was that it was of little use and undesirable, as a result of the resulting materials that the river water carries. About washing agricultural soil rich in nitrogenous and phosphate fertilizers and agricultural waste, in addition to the products of local activities such as wastewater or the use of detergents containing phosphate, which can be a source of phosphate contamination of surface water.